4mn-6m+5n-3m+4n-5mn=

Simple and best practice solution for 4mn-6m+5n-3m+4n-5mn= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4mn-6m+5n-3m+4n-5mn= equation:


Simplifying
4mn + -6m + 5n + -3m + 4n + -5mn = 0

Reorder the terms:
-6m + -3m + 4mn + -5mn + 5n + 4n = 0

Combine like terms: -6m + -3m = -9m
-9m + 4mn + -5mn + 5n + 4n = 0

Combine like terms: 4mn + -5mn = -1mn
-9m + -1mn + 5n + 4n = 0

Combine like terms: 5n + 4n = 9n
-9m + -1mn + 9n = 0

Solving
-9m + -1mn + 9n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-9n' to each side of the equation.
-9m + -1mn + 9n + -9n = 0 + -9n

Combine like terms: 9n + -9n = 0
-9m + -1mn + 0 = 0 + -9n
-9m + -1mn = 0 + -9n
Remove the zero:
-9m + -1mn = -9n

Combine like terms: -9n + 9n = 0
-9m + -1mn + 9n = 0

The solution to this equation could not be determined.

See similar equations:

| =x^2+19x+2 | | 2(x-3)-(x-2)=2x+3 | | 1-7y=-1 | | x-8.7=6.8 | | -9.3x=55.8 | | m+33=13 | | 24(2x-1)=6(x+3)+3 | | 2r=-8 | | =2-3x+2x^2-x^3 | | (4x-1)(x+2)=x(2x-3)-10 | | -8(2b+4)+(17b-6)=0 | | 2.5q-4.8-4.1q=-2.6q-4.7 | | 4-(2-3x)=6x-(4x+3) | | 0=-8+3z | | 2.5q-4.8q-4.1q=-2.6q-4.7 | | =2x^7+4x^6-6x^5+4x^4 | | 4(0)+y=-14 | | 4(-2)+y=-14 | | 4(-6)+y=-14 | | (y+3)(y+1)=2y(y+3) | | x^3-6*x^2+9*x-4=0 | | x^2-7x+264=0 | | x^2+8-7x+256=0 | | 36z^2-4=0 | | 1+8x=46-64x | | -0.2(x+3)=0.3(x+11) | | 9x(x)+47x+44=0 | | 2x(x)+x-2x-1=3x+6+9x | | 5x^2-60x+15=0 | | 3x^2+9x-36=0 | | a^2b-25b= | | 8x+0=72 |

Equations solver categories